The social network - Sorkin, Aaron; Fincher, David; Rudin, Scott, 1958-; Eisenberg, Jesse, 1983-; Garfield, Andrew, 1983-; Hammer, Armie, 1986-; Minghella, Max, 1985-; Timberlake, Justin, 1981-; Mara, Rooney; Reznor, Trent; Ross, Atticus, 1968-; Mezrich, Ben, 1969-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2011)
On a fall night in 2003, Harvard undergrad and computer programming genius Mark Zuckerberg sits down at his computer and heatedly begins working on a new idea. In a fury of blogging and programming, what begins in his dorm room soon becomes a global social network and a revolution in communication. A mere six years and 500 million friends later, Zuckerberg is the youngest billionaire in history, but for this entrepreneur, success leads to both personal and legal complications.
Disc 1. The film -- Disc 2. The supplements.
Based upon the book The accidental billionaires by Ben Mezrich.
DVD release of the 2010 motion picture.
Special features: Disc 1. Audio commentary with director David Fincher ; audio commentary with writer Aaron Sorkin & cast -- Disc 2. How did they ever make a movie of Facebook? (feature-length documentary in four parts) ; David Fincher and Jeff Cronenweth on the visuals ; Angus Wall, Kirk Baxter and Ren Klyce on post ; Trent Reznor, Atticus Ross and David Fincher on the score ; Ruby Skye VIP room (multi-angle scene breakdown) ; In the hall of the mountain king (Reznor's first draft) ; swarmatron.
Music, Trent Reznor & Atticus Ross ; editors, Angus Wall, Kirk Baxter ; director of photography, Jeff Cronenweth.
Jesse Eisenberg, Andrew Garfield, Armie Hammer, Max Minghella, Justin Timberlake.
MPAA rating: PG-13; for sexual content, drug and alcohol use, and language.
Keywords: Zuckerberg, Mark, -- 1984- -- Drama; Zuckerberg, Mark, -- 1984-; Facebook (Firm) -- Drama; Facebook (Firm); College students -- Drama; Social networks -- Drama; College students; Social networks; Fiction films; Feature films -- United States; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Biographical films; Historical films; Drama; Fiction films; Video recordings -- for people with visual disabilities; Video recordings -- for the hearing impaired